Evidence for selective imaging of different magnetic ions on the atomic scale by using a scanning tunnelling microscope with a ferromagnetic probe tip. - SHVETS, IGOR; COEY, JOHN MICHAEL DAVID (IOP Publishing, 1992)
Atomic resolution has been obtained on a magnetite (Fe3O4(001)) surface using a scanning tunnelling microscope with nonmagnetic tungsten and ferromagnetic iron tips. Selective imaging of Fe2 + and Fe3 + on B-sites is achieved by using the ferromagnetic Fe probe tip, reflecting the different spin configurations of the two magnetic ions. Local order in the distribution of Fe2 + and Fe3 + on the (001) surface is found at room temperature, well above the bulk order-disorder (Verwey) transition.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; Condensed matter; scanning tunnelling microscope